Correlating feedback capacity with degree of diffusion in heterogeneous complex networks. (1st January 2013) - Almohri, Sayed Mohammad; Al-Shiridah, Ghufran A.; Safar, Maytham; Mahdi, Khaled
Within non-hierarchal network, internal loop (cycle) structure exists that plays as a communication channel for feedback to enhance the social actor influence and contribution. A characteristic measure of network feedback capability is feedback capacity. At different penetrations away from a source of information, feedback capacity changes as the information diffuses. A measure of information diffusion is the degree of diffusion. It is the percentage of adopters and non-adopters during the diffusion process. In this work, we study the correlation between two innovative concepts to analyse complex networks based on the concepts of 'degree of diffusion' and 'feedback capacity' which are based on two different network characteristics 'degree' and 'cycles'. The correlation is found for different directed and undirected real complex networks and several undirected generated networks. The results show a second order polynomial correlation between the feedback capacity and the sum of the degree of diffusion and the network size.